A comment about estimable functions in linear models with non estimable constraints (1999)
In the Searle's (1987) book, Linear Models for Unbalanced Data, a characterization of the estimable functions in linear models with non estimable constraints is presented. In this informal paper, I indicate another characterization of these functions which was developed by Magnus and Neudecker (1988). The aim of the articte is to provide a caution signal to user of linear models theory.